A fronteira Brasil-França - Gutemberg de V. Silva; Aldomar A. Rückert (Confins)
The article analyses the political-institutional relation among Brazil and France with a focus on the State of Amapá, by the side of Brazil and the French Guiana by France. It begins with some considerations about the regional Geopolitics that has taken form during the times of limits drawing among the two countries, the only ones that connect a South American country and an European one. Next, geographical scales are used as a methodological resource to identify the complexity of contemporaneous international relations in their spatial dimension, stressing the pertinence of apprehension of reality in each of them. Next, it is identified elements that indicate the incorporation of new senses attributed to political frontiers in the context of international relations among Brazil and France, which basis is settled on many terms of institutionalized cooperation, which is a novelty in the 1990 decade if one consider that the focus is the frontier and that actions are for its development. Finally, the article presents some of the main obstacles for the advance of crossfrontier cooperation among Amapá and French Guiana. As a conclusion, it is suggested that the classic logics of political frontiers, of the discrete and isolation type has been changing for an environment of cooperation in different fronts, even with many obstacles to be surpassed in the spatial interactions among these two administrative unities.